2019
DOI: 10.32487/jtt.v7i1.637
|View full text |Cite
|
Sign up to set email alerts
|

Kenyamanan Lingkungan Termal Ruang Kuliah (C4) Fakultas Teknik Universitas Ichsan Gorontalo

Abstract: Kenyamanan termal suatu ruang kuliah diperlukan untuk mendukung proses penerimaan pembelajaran oleh mahasiswa. Penelitian ini bertujuan untuk mengetahui kenyamanan lingkungan termal pada ruang kuliah (C4) Fakultas Teknik Universitas Ichsan Gorontalo dengan menggunakan sistem penghawaan buatan (AC). Kuisioner dibagikan kepada 30 mahasiswa Teknik Arsitektur dengan menggunakan sensasi termal ASHRAE, penerimaan kondisi termal serta preferensi termal. Bersamaan dengan itu dilakukan pengukuran lapangan untuk mengeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on previous thermal comfort study data, it can be concluded that at 29ºC, the residents of Gorontalo City begin to feel discomfort, with the peak heat sensation at 33ºC. 5 [6]. Therefore, based on the temperature decrease achieved by the Eco-Cooler, ranging from 26.65ºC to 27.05ºC, it can be inferred that the Eco-Cooler is capable of providing a comfortable or neutral sensation for room occupants…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on previous thermal comfort study data, it can be concluded that at 29ºC, the residents of Gorontalo City begin to feel discomfort, with the peak heat sensation at 33ºC. 5 [6]. Therefore, based on the temperature decrease achieved by the Eco-Cooler, ranging from 26.65ºC to 27.05ºC, it can be inferred that the Eco-Cooler is capable of providing a comfortable or neutral sensation for room occupants…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, only 3.13% of the participants selected the warm sensation, and an equal percentage chose the cold sensation. [6] The utilization of wind as a means to enhance the indoor thermal comfort proves to be a successful approach. An instance of its application is the implementation of the Eco-Cooler, which operates on the fundamental principle of the first law of Thermodynamics.…”
Section: Introductionmentioning
confidence: 99%